Evaluation and Implementation of PG 76-22 Asphalt Rubber Binder in Florida. Issue 1 (January 2015) - Greene, James; Chun, Sanghyun; Nash, Tanya; Choubane, Bouzid
The Florida Department of Transportation (DOT) has had a long history of recycling ground tire rubber (GTR) from waste tires in highway projects. The Florida DOT first experimented with asphalt rubber binder (ARB) more than 35 years ago. In 1988, the Florida legislature mandated the investigation of using recyclable materials such as GTR in roadway construction. For more than 25 years, the Florida DOT has effectively satisfied the intent of the legislature. However, the ARB has often been associated with unpredictable performance and handling issues, such as the separation of the GTR from the binder. These performance and handling issues have resulted in higher construction costs and have made ARB less appealing because a more reliable alternative, PG 76-22 polymer modified asphalt (PMA), is available. As a result, a task team of the Florida DOT and industry members was formed with the goal of finding a way to make ARB handle and perform similarly to PG 76-22 (PMA), Florida's gold standard binder. This paper documents an accelerated pavement testing (APT) study to compare hot-mix asphalt mixtures constructed with PG 76-22 (PMA) and PG 76-22 (ARB). This APT study represents the final stage of the implementation of a new PG 76-22 (ARB) specification.